Involvement of CCL2 and CH25H Genes and TNF signaling pathways in mast cell activation and pathogenesis of chronic spontaneous urticaria - Fang, Xiaobin; Weng, Yueyi; Zheng, Xiaochun (Frontiers in Immunology, 2023)
Chronic spontaneous urticaria (CSU), a mast cell-driven disease, substantially affects the quality of life. While genetics affect CSU susceptibility and severity, the specific genetic factors associated with mast cell activation in CSU remain elusive. We aimed to identify key genetic factors and investigate their roles in CSU pathogenesis. Two gene expression datasets from the Gene Expression Omnibus were merged and validated using principal component analysis and boxplots. The merged dataset was subjected to limma and weighted gene co-expression network analyses. Genes whose expression correlated highly with CSU were identified and analyzed using Gene Set Enrichment Analysis (GSEA), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. As GSEA, GO, and KEGG analyses highlighted the importance of chemokine (C-C motif) ligand 2 (CCL2) and cholesterol 25-hydroxylase (CH25H) gene and tumor necrosis factor (TNF) signaling pathways in CSU; the three corresponding genes were knocked down in human mast cell line-1 (HMC-1), followed by incubation with thrombin to mimic CSU pathogenesis. CCL2, CH25H, and TNF knockdown reduced excitability and cytokine production in HMC-1. Our findings suggest that genes involved in the CCL2, CH25H, and TNF pathways play crucial roles in CSU pathogenesis, providing insights into potential therapeutic targets for CSU treatment.